FAKTORFAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA WANITA USIA SUBUR DI PUSKESMAS UMBULHARJO I YOGYAKARTA TAHUN 2009 - Yeni, Yufita; Djannah, Sitti Nur; Solikhah, . (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2010)
Background: Hypertension or high blood pressure is heart and blood vessel disorder marked by increasing of blood pressure. Consequence from this incident is occurrence of other accompanying illness. Hypertension may occur in people without age and sex limitation until it needs good handling. High prevalence of childbearing age woman suffer from hypertension in Puskesmas Umbulharjo I (Public Health Service) has drove writer to make study about factors related with hypertension incident in childbearing age woman in Puskesmas Umbulharjo I Yogyakarta. Objective of this research is to recognize correlation between history of hypertension family, obesity, and hormonal contraception usage, and hypertension incident of childbearing age woman in Puskesmas Umbulharjo I Yogyakarta. Method: This was observational analytic research using cross sectional approach. Population of this study is age group which medicinize in common polyclinic of Puskesmas Umbulharjo I Yogyakarta. Sample was taken using Accidental Sampling method. Sample comprised of childbearing age woman who suffering hypertension (having problem) and those who have not hypertension problem (having not problem), and meet respondent inclusion criterion, that resulted of 88 women. Result: Result of this study showed there is no correlation between history of hypertension family with hypertension incident, that is p=0,158, > ?=0,05, calculated chi square is 1.992 < tabulated chi square of 3,481. There is correlation between obesity and hypertension incident with p value of 0,007 < ?=0,05, and calculated chi square is 7,298 > tabulated Chi Square of 3,481. There is no correlation between hormonal contraception and hypertension incident with value of p= 0,762 > ?=0.05, and calculated Chi Square of 0.091 < tabulated Chi Square of 3,481. Conclusion: There was no correlation between history of hypertension family and hormonal contraception with hypertension incident. There is correlation between obesity and hypertension incident. Keywords: hypertension, history of hypertension family, obesity, hormonal contraception.